[OP.1A.06] DOES DIABETES REALLY HARM WOMEN MORE THAN MEN? ANALYSES FROM 30560 INDIVIDUAL PATIENT DATA. (September 2017) - Le, H.; Subtil, F.; Cerou, M.; Marchant, I.; Lindholm, L.; Thijs, L.; Gueyffier, F.
Abstract : Objective: Men are more likely than women to develop type 2 diabetes. However, women with diabetes are at higher risk of morbidity and mortality from diabetes complications. We aimed to explore here the interaction between gender and type 2 diabetes in terms of common cardiovascular outcomes from 30 560 individual patient data. Figure. No caption available. Design and method: We used the proportional hazards regression Cox model to examine this interaction separately and in combination with other significant risk factors, i.e in corresponding univarible and multivariable analyses. Data was collected from seven randomized controlled trials including Coope, EWPHE, MRFIT, SHEP, STOP, SYSTEUR (INDANA database) and DIABHYCAR. Patients included were hypertensive, with or without type 2 diabetes and some cardiovascular histories, aged range 35–98. Maximum duration of follow-up was 11.87 years (mean 4.97 years). Studied cardiovascular outcomes were sudden death, total death, cardiovascular death, fatal myocardial infarction, stroke and coronary heart disease. Results: Diabetes and male sex always represented significantly higher risks for sudden death, total death, cardiovascular death, fatal myocardial infarction, stroke and coronary heart disease in both univariable and multivariable analyses, except male sex for stroke in corresponding multivariable analysis. Their interaction was significant for all outcomes except coronary heart diseases in univariable analyses and except cardiovascular death, stroke and coronary heart diseases in multivariable analyses (Tab.1). On average, women with diabetes had 85% higher risk of sudden death, 23% higher risk of total death and 24% higher risk of fatal myocardial infarction than diabetic men, all in a significant way. The same tendency was observed for cardiovascular death, stroke and coronary heart diseases but these results were not statistically significant (Tab.2). Conclusions: In our database, the interaction between gender and type 2 diabetes was significant in terms of sudden death, total death and fatal myocardial infarction with adjustment by treatments, trials, age, smoking status, systolic blood pressure, total cholesterol and history of myocardial infarction. Our observations were in accordance with the literature: for non-diabetic subjects, men represented 1.5 to 2.3 times higher risk for studied endpoints; however, for diabetic ones, women seemed to have worse cardiovascular outcomes.